Implementasi Rencana Tata Ruang Wilayah Kota Jayapura terhadap Peruntukan Lahan di Holtekamp Distrik Muara Tami - Jhon Ronaldo Naa; Marsal Arung Lamba; Lazarus Ramandei; Tommi Tommi (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Law of the Republic of Indonesia Number 26 of 2007 concerning Spatial Planning indicates that the preparation of spatial planning plans must cover land space, sea space and air space, including space inside the earth, arranged in stages and ultimately the spatial planning plan is determined with their respective regional regulations. The method used in the research is the survey method. The type of research used is quantitative and descriptive qualitative research. Meanwhile, the quantitative approach results from the public's perception that the results of existing research show a variety of public attitudes and views towards government policies, ranging from full support to dissatisfaction. Based on the spatial plan on the Jayapura City Cultivation Area Plan Map for 2023-2033, there are 7 (seven) namely Convertible Forest Land, Protected Area, Livestock Land Area, Fishery Area, Limited Production Forest Area and Food Crop Area, from the results of a survey conducted by author at the research location there have been changes in the Convertible Forest land area as a result of development activities and the reduction in land area in the Cultivation Area which initially had an area of ​​523,847 Ha, has been reduced to 523,790 or 0.01%, where housing has a larger area, namely 13,665 Ha. And land changes have also occurred in the Limited Production Forest Area, which initially had an area of ​​430,048 Ha, has undergone changes and been reduced to 121,027 Ha or 14%, this is because there is agricultural land with an area of ​​19,409 Ha in the Limited Production Forest Land area experiencing changes. which is quite big.